KINERJA PROTOTIPE RODA PENGGERAK BERSIRIP GANDA PADA LAHAN SAWAH GAMBUT - Susanto, Herdi; Darsan, Herri; Jayadi, Farid; Masykur, Masykur; Husin, Zakir; Ali , Syurkarni (Jurnal Rekayasa Mesin, 2024)
Agricultural technology to support the agricultural sector, especially peaty paddy fields, should be developed, because peat land with a thickness of less than one meter has been recommended for rice crops. supported by a potential peatland area of ​​up to 21 million Ha or 10.8% of Indonesia's land area. Currently, peatland farming communities use sickles to harvest rice and hoes to cultivate the land. So far, hand tractor finned wheel drive technology has been widely used for cultivating wet paddy fields, whereas in conditions of peaty paddy fields it has not been able to be used because of the high level of sinkage and wheel slip, for this reason a new model of wheel is needed that is capable of working in peaty paddy fields. The aim of the research is firstly to find the right model of driving wheel for use in peaty paddy fields, secondly a prototype driving wheel for peaty paddy fields, and thirdly to experimentally test the driving wheel. Research results (1) prototype with a driving wheel diameter of 35 cm and the number of fins is 8 for the standard fin type and for the double fin type the driving wheel diameter is 40 cm with 4 vertical arc fins, which are placed on the surface of the driving wheel. (2) Comparison with the same type of loading shows that the double fin type drive wheel has a relatively smaller level of wheel loading (around 20%) when compared to the standard type drive wheel. (3) The sinkage level of the standard type drive wheel has a smaller sinkage (around 10%) compared to the double finned wheel type, in tests with the same type of loading. test loads for wheels are 20 kg, 40 kg and 60 kg. The double fin type drive wheel is good for use in peaty paddy fields.